2020
DOI: 10.14295/bds.2020.v23i1.1824
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of marginal fit and microleakage of monolithic zirconia crowns cemented by bio-active and glass ionomer cements: In vitro study

Abstract: Objective: To evaluate the marginal fit and microleakage of monolithic zirconia crowns cemented with bioactive cement (Ceramir) compared to that cemented with glass ionomer cement and to evaluate the effect of thermocycling on marginal fit. Materials and methods: Twenty sound human molar teeth were prepared to receive a monolithic zirconia crowns. Teeth were divided randomly into two equal groups according to the type of luting cement. Group I: glass ionomer cement and group II: Ceramir cement. After c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…All the tested occlusal veneers marginal gap results were within the range of the clinically accepted value below 50 µm [19] . [20] .…”
Section: Discussionsupporting
confidence: 58%
“…All the tested occlusal veneers marginal gap results were within the range of the clinically accepted value below 50 µm [19] . [20] .…”
Section: Discussionsupporting
confidence: 58%
“…A previous study by Emtair et al [ 15 ] concerning the effect of axial convergence on the marginal fit of CAD/CAM zirconia copings showed that marginal fitness was improved by increasing the tapering degree of prefabricated dies. Marginal fit and microleakage of monolithic zirconia crowns cemented by bioactive and glass-ionomer cement were compared in a study by Aboelenen et al [ 17 ]. They found that similarity in the physical properties and chemical composition of the two types of cement resulted in a nonsignificant effect on the extent of microleakage.…”
Section: Introductionmentioning
confidence: 99%
“…Sesame oil's high phosphorus and calcium content may chemically bind with the calcium in tooth structure to improve adherence. [31] Nano bioactive ceramics improved GIC mechanical properties and dentin bond strength, according to Panigrahi et al [32]. Standard GICs are given HA to enhance their mechanical properties [33].…”
Section: Discussionmentioning
confidence: 99%